BET 1: Prone positioning of awake patients with acute hypoxaemic respiratory failure. Issue 6 (2nd June 2020) - Bell, Jack; Horner, Daniel
Abstract : A short-cut review of the literature was carried out to examine the potential utility of prone positioning in awake patients with hypoxaemic respiratory failure. Four papers were identified as suitable for inclusion using the reported search strategy. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of the best papers are tabulated. It is concluded that there is no evidence that regular prone positioning in the awake patient with hypoxaemic respiratory failure impacts on clinically relevant outcomes. Further research is required to evaluate the safety and effectiveness of this intervention, compared with routine mobilisation strategies.